Pemanfaatan Limbah Organik dengan Eco Enzym sebagai Upaya Mewujudkan Lingkungan Sehat di Kelurahan Menteng - Adelia, Kadek Ayu Cintya; Ety Kurniati (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
Organic waste that is not managed properly can cause various environmental problems, such as unpleasant odors, water and soil pollution, and an increase in the population of disease vectors. This community service aims to introduce and train residents of Menteng Village in the utilization of organic waste into eco enzymes as an environmentally friendly solution. Eco enzymes are organic waste fermentation products that have various benefits, including as a natural cleaner, liquid organic fertilizer, and water purifier. This community service activity includes socialization about the benefits of eco enzymes, training in making eco enzymes from fruit and vegetable waste, and demonstrations of the use of eco enzymes in everyday life. In addition, we also provide assistance to residents in implementing sustainable eco enzyme manufacturing practices. The results of this activity show an increase in awareness and knowledge of Menteng Village residents about organic waste management and the benefits of eco enzymes. Residents also showed high enthusiasm in practicing making eco enzymes in their respective homes. It is hoped that this activity can contribute to reducing the volume of organic waste in Menteng Village, creating a cleaner and healthier environment, and increasing community independence in waste management.